History and actual problems of organ donation - G.I. Kovtun; B.M. Todurov; O.A. Kanyura (Кардіохірургія та інтервенційна кардіологія)
The review is devoted to the history of the development of organ transplantation and the analysis of models of organ transplantation in countries that are leaders in the field of transplantation. Organs transplantation abroad has become an effective method of treatment that saves lives, but it is also an indicator of the success of the country’s development as a whole, an important element of national pride and prestige. However, performing transplantations is associated with problems of an organizational, as well as legal, moral and ethical nature. The main problem is a shortage of donor organs. The review analyzes measures aimed at increasing the level of donation in the world and promoting the development of transplantology.